2016
DOI: 10.1007/s40519-016-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of orthorexia nervosa among German students using the 21-item-DOS

Abstract: The prevalence of ON appears to be low in this sample of German university students. Female NS students do not seem to have higher prevalence of ON or risk of developing ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 28 publications
3
41
1
4
Order By: Relevance
“…Indeed, the suitability of some of the items has been debated by some researchers, for example, Missbach et al [ 13 ] who question whether item 1 regarding calories provides valid information, considering that, generally speaking, a person with orthorexia is considered to worry more about the quality of food as opposed to the quantity of the same. Likewise, the idea that orthorexia may be a subphase within the healing process of other eating disorders such as anorexia, as other research has suggested [ 33 , 34 ], may favor the inclusion of this item. The many divergent study results and clinical opinions about ON suggest that the scientific and medical communities must continue to work together toward a clearer understanding of the disorder and its symptoms, as well as for the development of a more reliable standard screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the suitability of some of the items has been debated by some researchers, for example, Missbach et al [ 13 ] who question whether item 1 regarding calories provides valid information, considering that, generally speaking, a person with orthorexia is considered to worry more about the quality of food as opposed to the quantity of the same. Likewise, the idea that orthorexia may be a subphase within the healing process of other eating disorders such as anorexia, as other research has suggested [ 33 , 34 ], may favor the inclusion of this item. The many divergent study results and clinical opinions about ON suggest that the scientific and medical communities must continue to work together toward a clearer understanding of the disorder and its symptoms, as well as for the development of a more reliable standard screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration only the DOS with its proposed cutoff (score ≥ 30) the prevalence of ON in a representative German sample was estimated to be 6.9% [25]. Additional findings have revealed that the prevalence rate of ON among university students was 3.3% in a German sample [26], 7.8% in a Chinese sample [24], 8% in a U.S. sample [22] and 10.5% in a Spanish sample [23].…”
Section: Introductionmentioning
confidence: 94%
“…So scheint die ursprüngliche Beobachtung und Annahme, dass ON üblicherweise bei Männern auftritt [12], so nicht mehr haltbar. Wenige Studien zeigen entweder erhöhte Werte bei Männern [2,28,78] oder Frauen [24,29,43,68,73,79], die überwiegende Mehrzahl ( > 20 Studien) deutet jedoch auf ähnliche Fallzahlen bzw. vernachlässigbare Unterschiede, z.…”
Section: äTiologie (Sozio-) Demografie Und Bmiunclassified